Evaluation of the Effect of Topical Application of Nigella sativa on Acute Radiation-Induced Nasal Mucositis - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2018)
The goal of this study was to demonstrate the effect of radiotherapy (RT) on nasal mucosa in rats and to evaluate the radioprotective effects of the topical application of black seed oil (Nigella sativa [NS]) to treat acute radiation-induced nasal mucositis.A total of 18 rats were randomized into 3 groups, with 6 animals per group. The rats in group 1 were topically administered saline in the nasal cavity after sham irradiation. Group 2 received saline at the same dose after irradiation. Group 3 was given NS after irradiation. The rats in groups 2 and 3 were irradiated with a single dose of 40 Gy to the nasal and paranasal area. Only one drop of saline (0.05 mL) was applied to each nostril in the first, second, and third days after RT in groups 1 and 2. One drop of cold press NS (0.05 mL) was applied to each nostril in group 3. Fourteen days after irradiation, the nasal mucosal tissues were excised for histopathological evaluation. Vascular dilatation, inflammatory cell infiltration, superficial erosion, and formation of exudates were classified according to the severity.No evidence of mucositis was observed in group 1. Of all the parameters the only statistically significant difference between groups 2 and 3 were observed for superficial erosion (P<0.05). Overall microscopic observations in the NS-treated group were better than in group 2.The preliminary results of our study have shown that local application of NS to the nasal mucosa may be an effective treatment of acute nasal mucositis due to RT.
Keywords: Antioxidant agents; mucositis; Nigella sativa; radiotherapy; INDUCED ORAL MUCOSITIS; CANCER; AMIFOSTINE; THYMOQUINONE; RADIOTHERAPY; HEAD; OIL; CONSTITUENT; CARCINOMA; DAMAGE